Neonatal hydrometrocolpos: a clinical case of difficult diagnosis - Tang Ploog, Luis Eduardo (2021)
The diagnosis of fetal malformations continues to be a challenge for the obstetrician-gynecologist, despite advances in fetal medicine and ultrasonographic technology. Hydrometrocolpos is a dilatation of the uterus and vagina due to accumulation of secretions, product of genital obstruction usually associated with congenital malformations. We present the case of a female newborn with congenital hydrometrocolpos, whose diagnostic suspicion in pelvic studies was ovarian cysts, but it was due to the increase of bilateral hydronephrosis. At birth, it was decided to surgically decompress the urinary tract, at which time hydrometrocolpos associated with imperforate hymen was found.